The Impact Of Concerts, Music Festivals, And Nightlife On Work-Life Balance And Work Productivity Among Generation Z - Sukamto, Irvan Mahidin; Adhi Triachmadi , Mumin; Rahmanita, Mryza; Erica Panjaitan, Liza; Mishell (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Study This to study influence attendance at concerts , music festivals and clubs Evening to productivity Work Generation Z in Jakarta, with work-life balance as variable mediation . Although participation in entertainment music the more popular , research about the impact to results Work Still limited . Research This involving 400 workers full time from Generation Z chosen using stratified random sampling based on experience they attend a music event in six month last . Analysis done with Structural Equation Modeling For test connection between variables . Research results show that frequency participation in concerts ( β = 0.204, p < 0.001), music festivals ( β = 0.241, p < 0.001), and clubs night ( β = 0.255, p < 0.001) has an effect significant to productivity work . Influence the mediated partially by increasing work-life balance ( mediation) β between 0.122 to 0.166, p < 0.05), which shows that music event functioning as means recovery psychological and improvement motivation . Findings This expanding the work-life balance model by enter entertainment as factor Supporter recovery psychological and improvement performance in Generation Z. In general practical , organization recommended For integrate activity music in welfare programs employees , such as subsidy ticket concerts , internal music events , or policy Work flexible . For makers policy , results This support development MICE and tourism sector music through supportive regulations , convenience​ licensing , and improvements capacity industry entertainment . Limitations study This covering use of self-report data and cross-sectional design . The study advanced recommended use longitudinal approach